Using Literacy Strategies to Support a Preservice Teacher Candidate in Becoming an Effective Teacher (Journal of Education and Development, 2022)
This qualitative investigation used a case study approach to collect data to answer this question: Did a preservice teacher candidate enrolled in a content literacy course while seeking initial middle-level teacher certification find literacy strategies useful in the instruction of seventh-grade science students? This study reports findings collected from one preservice teacher candidate, along with course peers, seeking initial certification for middle-level instruction. Data collection included an interview, member checking, and observations. Over the fifteen-week period of instruction in an undergraduate content literacy course, data provided evidence that literacy strategies used by a preservice teacher candidate in the instruction of science for middle-level students provided effective acquisition of instructional content.